Neuro-glyo-capillary interactions between the sciatic nerve and its segmental centers at the experimental etoposide-induced neuropathy - N. Yu. Luchkiv (Zaporožskij Medicinskij Žurnal)
The neurological symptoms that appear during therapy are sufficiently described in the literature, but the long-term results require a more detailed study, as systematic studies of the pathogenesis of toxic neuropathy that have arisen as a result of chemotherapy are few.